Agriculture, the Environment, and Social Complexity From the Early to Late Yangshao Periods (5000–3000 BC): Insights From Macro-Botanical Remains in North-Central China - Li, Yaping; Zhang, Junna; Zhang, Xiaohu; Zhao, Haitao (Frontiers in Earth Science, 2021)
In northern China, the Yangshao cultural period (5000-3000 BC) was a critical timespan in the establishment of agricultural economies and the emergence of social complexity. We present the results of archaeobotanical analysis from 58 soil samples collected from 12 recently investigated sites located in the Luoyang Basin, and recovered 5290 carbonized plant remains from 9 sites dating to the Late Yangshao period. We compared our novel dataset with previous archaeobotanical date, compiling a total of 196 samples from 58 sites in central and western Henan Province. During the Early Yangshao period (5000-4200 BC), a nascent, extensive agricultural economy based primarily on broomcorn millet, with lesser foxtail millet and rice, was developing in small settlements (<0.2 km2) in the loess tablelands and valleys of western Henan province. However, the population pressure—rather than environmental degradation—drove the “foxtail millet-broomcorn millet substitution” during the Middle Yangshao period (4200-3500BC). The intensive agriculture based mainly on foxtail millet facilitated the development of social complexity in the region, as demonstrated by the emergence of size-graded agricultural settlements of medium (0.2-0.6 km2) and large (>0.6 km2) scale. Notably, millets tend to be less ubiquitous in these larger settlements compared to smaller ones, with differences in millet ubiquity between sites increasing over time. The local surface hydrology influenced by paleoclimatic changes prompted the spread of agriculture from higher loess tablelands and valleys during the early Yangshao period into more marginal loess tablelands and plains by the Middle and Late Yangshao periods. Rice cultivation is concentrated in valley areas and appears to have been closely tied to environments with better hydrothermal conditions. Our research shows that climatic conditions during the Holocene fostered the development of agriculture during the Yangshao Culture period and that the distribution of settlements throughout this time was influenced by highly localized geomorphologic environments delimiting the distribution of crops. The rise of agriculture promoted the formation of complex and stratified economies in the Yangshao Culture period and it was the intensification and elaboration of these new economic and social systems that led to later transformation in agricultural structures and settlement sizes.